SPATIAL ANALYSIS FOR MICROPLANNING TO ADDRESS IMMUNIZATION INEQUALITIES IN INDONESIA - Astutik, Erni; Hargono, Arief; Artanti, Kurnia Dwi; Hidajah, Atik Choirul; Husnina, Zida; Sari, Siti Shofiya Novita; Sitohang, R. Vensya; Surya, Asik; Hapsari, Ratna Budi; Feletto, Marta (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: To achieve high and equitable immunization coverage, it is important to understand the access and utilization barriers, as well as the influencing determinants among population groups. Aims: This study aims to identify high-risk regencies and explore the application of spatial analysis to support microplanning in immunization programs. Methods: This study employed an implementation research design conducted in Aceh Province, Indonesia. Secondary datasets on immunization coverage, health human resources, facilities, and socio-economic parameters were analyzed. Focus group discussions (FGDs) and training sessions were conducted with health workers. Results: The average coverage of universal child immunization (UCI) across villages was 24.18%, while complete basic immunization (CBI) reached 55.85%. In general, regencies with low UCI and CBI often had limited human resources, inadequate health facilities, and a high proportion of high-risk populations. This study identified hot spots and cold spots in the study area. Additionally, participants reported that mapping using the application was easier and beneficial for supporting the preparation of immunization micro-planning. Conclusion: Spatial analysis can help address inequalities in immunization services and support resources during immunization. Qualitative approaches provided a deeper understanding of undocumented information. The use of mapping applications facilitated more effective microplanning in immunization programs. Keywords: Child mortality, health risk, immunization, microplanning, vaccine.